2013
DOI: 10.1017/s1368980013000116
|View full text |Cite
|
Sign up to set email alerts
|

Which dimensions of food-related lifestyle are likely to be associated with obesity in Italy?

Abstract: Objective: To compare obese v. non-obese consumers in terms of their general food-related lifestyles and to explore possible food-related factors affecting obesity in Italy. Design: The data were collected using a self-completion questionnaire. Data included sociodemographic information, measures of the Food-Related Lifestyle scale (FRL) and self-reported weight and height. A logistic regression model was fitted for the sample with obesity as the dependent variable and sociodemographic characteristics and FRL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…The main premise of the relationship between satisfaction and behavior rests on the theory of attitude formation in consumer conations, which is largely influenced by affective responses such as satisfaction (Ji et al, 2016). The role of satisfaction in predicting purchase intentions is well established, and research has shown that higher levels of satisfaction lead to strong purchase intentions for certain foods (Saba, Cupellaro, & Vassallo, 2014).…”
Section: Satisfactionmentioning
confidence: 99%
“…The main premise of the relationship between satisfaction and behavior rests on the theory of attitude formation in consumer conations, which is largely influenced by affective responses such as satisfaction (Ji et al, 2016). The role of satisfaction in predicting purchase intentions is well established, and research has shown that higher levels of satisfaction lead to strong purchase intentions for certain foods (Saba, Cupellaro, & Vassallo, 2014).…”
Section: Satisfactionmentioning
confidence: 99%
“…The questionnaire contained questions commonly used in consumer research studies (Saba, Cupellaro, & Vassallo, 2013). The questionnaire was separated into two parts; the first part was administered prior to the meal and contained information about age, level of appetite, educational achievement and self-reported height (cm) and weight (kg).…”
Section: Questionnaire Developmentmentioning
confidence: 99%
“…The food-related lifestyle (FRL) tool interprets the lifestyles to include experience based on subjective perception, experience and information available to the consumer on products. FRL also involves in the configuration of values, the objective procedures that the consumers use to obtain, use and their feeding behaviour (Aarset et al , 2004; Saba et al , 2014). The FRL interpretation thus describes a mindset that frames consumer behaviour and goes beyond the actions of individual behaviour (Brunsø et al , 2004).…”
Section: Introductionmentioning
confidence: 99%